Pengaruh Persepsi Siswa Tentang Kompetensi Pedagogik Guru Dan Motivasi Belajar Siswa Terhadap Hasil Belajar Al-Qur'an Hadis Siswa Kelas Viii Mts Darul Ulum Semarang - Wahyu Rizal Saputra; Nur Asiyah; Kasan Bisri (Gunung Djati Conference Series, 2022)
The general objective of this research is to find and analyze empirically the effect of students perceptions on teacher pedagogical competence and learning motivation of students together on the learning achievement of Al-Qur’an Hadis students. This research is a descriptive quantitative research. Data were collected on class VIII students at MTs Darul Ulum Semaranng and the subjects selected in this research were three class. The data collection techniques used were students perceptions on teacher pedagogical competence questionnaire, student learning motivation questionnaire, recapitulation of student learning achievement and documentation. The data analysis techniques used are percentage analysis techniques, data normality test, data linearity test, simple linear regression analysis, double regression analysis and significance test. The validity of the data uses the product moment correlation formula and reliability uses the Alpha Cronbach formula. In this research, Microsoft Excel were used to help process and analyze research data. The results of this research indicate: (1) The influence of student perceptions of teacher pedagogic competence on student achievement (2) The influence of learning motivation on student achievement (3) There was a significant influence on student perceptions of teacher pedagogic competence and learning motivation together on the learning achievement of Al-Qur’an Hadis students.